Smith-Magenis syndrome: a new contiguous gene syndrome. Report of three new cases. Issue 9 (September 1991) - Moncla, A; Livet, M O; Auger, M; Mattei, J F; Mattei, M G; Giraud, F
Abstract : Interstitial deletion of the short arm of chromosome 17 was detected in three patients. They all had a similar phenotype with mental retardation, behavioural problems, facial dysmorphism, brachycephaly, a broad face with a flat midface, and short and broad hands. All three cases were ascertained over a six month period by two neuropaediatricians aware of this specific anomaly, which suggests that this microdeletion is not particularly rare. Comparison of the clinical and cytogenetic findings in a total of 24 patients allows a new contiguous gene syndrome to be defined that only high resolution analysis can detect. In two cases, molecular analysis confirmed the cytogenetic results. The Charcot-Marie-Tooth type Ia gene has recently been localised to the 17p11.2 sub-band.